2009
DOI: 10.1152/ajpendo.00374.2009
|View full text |Cite
|
Sign up to set email alerts
|

Increased basal level of Akt-dependent insulin signaling may be responsible for the development of insulin resistance

Abstract: A majority of subjects with insulin resistance and hyperinsulinemia can maintain their blood glucose levels normal for the whole life presumably through protein kinase B (Akt)-dependent insulin signaling. In this study, we found that the basal Akt phosphorylation level was increased in liver and gastrocnemius of mice under the high-fat diet (HFD). Levels of mitochondrial DNA and expression of some mitochondrion-associated genes were decreased by the HFD primarily in liver. Triglyceride content was increased in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
86
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(101 citation statements)
references
References 50 publications
14
86
1
Order By: Relevance
“…It is important to note that our findings are consistent with previous studies showing that basal Akt phosphorylation at threonine 308 and serine 473 is increased in skeletal muscle and liver of high fat diet-induced diabetic rodents (36,37) and Zucker (fa/fa) rats (38), although insulin-stimulated Akt phosphorylation is attenuated in these animals. The authors argued that increased basal Akt phosphorylation in insulin-resistant rodents might result from hyperinsulinemia (37,38), although tyrosine phosphorylation of IR, IRS-1, or IRS-2 was not examined in their studies. However, our data do not exclude the possibility that as yet unclarified factors other than hyperinsulinemia may also contribute in concert to the increased basal phosphorylation of IRS-1 and Akt in both liver and muscle of L-iNOS-Tg mice, based on the following observations.…”
Section: Volume 286 • Number 40 • October 7 2011supporting
confidence: 92%
“…It is important to note that our findings are consistent with previous studies showing that basal Akt phosphorylation at threonine 308 and serine 473 is increased in skeletal muscle and liver of high fat diet-induced diabetic rodents (36,37) and Zucker (fa/fa) rats (38), although insulin-stimulated Akt phosphorylation is attenuated in these animals. The authors argued that increased basal Akt phosphorylation in insulin-resistant rodents might result from hyperinsulinemia (37,38), although tyrosine phosphorylation of IR, IRS-1, or IRS-2 was not examined in their studies. However, our data do not exclude the possibility that as yet unclarified factors other than hyperinsulinemia may also contribute in concert to the increased basal phosphorylation of IRS-1 and Akt in both liver and muscle of L-iNOS-Tg mice, based on the following observations.…”
Section: Volume 286 • Number 40 • October 7 2011supporting
confidence: 92%
“…Autophagy markers were detected as detailed above. Results showed that the basal level of Akt phosphorylation was increased by the HFD as we previously described (28) but reversed by the treatment with LY294002 (supplemental Fig. 1, A and B).…”
Section: Hepatic Expression Of Key Genes Involved In Activation Of Ausupporting
confidence: 77%
“…To explore whether or not insulin signaling was responsible for the suppressed autophagy in the presence of insulin resistance/hyperinsulinemia, insulin resistance in mice was induced by the HFD (4 weeks) as we previously described (28). Some mice were administered the phosphatidylinositol 3-kinase inhibitor LY294002 during day time (once a day for the last week), when mice normally sleep and do not eat.…”
Section: Hepatic Expression Of Key Genes Involved In Activation Of Aumentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, hCRP was associated with a significant increase in basal Akt Ser 473 phosphorylation. Previous studies have implicated high-level basal Akt Ser 473 phosphorylation in insulin resistance in the liver and muscle in mice 37 and in low glucose uptake in the heart in diabetic rats. 38 The difference observed between insulin-induced phosphorylation of Akt Ser 473 and Thr 308 is in part due to the significantly different basal phosphorylation levels of the two sites, as suggested previously.…”
Section: Discussionmentioning
confidence: 97%